2009
DOI: 10.1002/tox.20483
|View full text |Cite
|
Sign up to set email alerts
|

Amifostine protection against induced DNA damage in γ‐irradiated Escherichia coli cells depend on recN DNA repair gene product activity

Abstract: Amifostine is the most effective radioprotector known and the only one accepted for clinical use in cancer radiotherapy. In this work, the antigenotoxic effect of amifostine against gamma-rays was studied in Escherichia coli cells deficient in DNA damage repair activities. Assays of irradiated cells treated with amifostine showed that the drug reduced the genotoxicity induced by radiation in E. coli wild-type genotypes and in uvr, recF, recB, recB-recC-recF mutant strains, but not in recN defective cells. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It has been known that amifostine/WR-1065 can directly support DNA repair (Figure 10) by donating hydrogen atoms and depleting oxygen to a singlet state. 53 Further, Almeida et al 20 revealed that the protection by amifostine against radiation-induced genotoxicity in Escherichia coli cells depends on the functional recN gene that is essential for the SOS response and repair of DSBs by homologous recombination. Dziegielewski et al 54 showed that WR-1065 prevents delayed genomic instability though, contrary to Almeida et al, 20 these authors suppose that WR-1065 disrupts homologous recombination and prevents its dangerous hyperstimulation by ionizing radiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been known that amifostine/WR-1065 can directly support DNA repair (Figure 10) by donating hydrogen atoms and depleting oxygen to a singlet state. 53 Further, Almeida et al 20 revealed that the protection by amifostine against radiation-induced genotoxicity in Escherichia coli cells depends on the functional recN gene that is essential for the SOS response and repair of DSBs by homologous recombination. Dziegielewski et al 54 showed that WR-1065 prevents delayed genomic instability though, contrary to Almeida et al, 20 these authors suppose that WR-1065 disrupts homologous recombination and prevents its dangerous hyperstimulation by ionizing radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Almeida et al revealed that the protection by amifostine against radiation-induced genotoxicity in Escherichia coli cells depends on the functional recN gene that is essential for the SOS response and repair of DSBs by homologous recombination. Dziegielewski et al showed that WR-1065 prevents delayed genomic instability though, contrary to Almeida et al, these authors suppose that WR-1065 disrupts homologous recombination and prevents its dangerous hyperstimulation by ionizing radiation. In any case, direct interactions of the drug with p53, NFκB, ATM, and Tip60 (Xu et al), together with the modified expression of genes involved in DNA repair, cell cycle regulation, and apoptosis confirm a more general influence of amifostine (and its metabolites) on DSB repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, amifostine has been applied for clinical protection against xerostomia during radiotherapy of head and neck cancer [103] . Interestingly, in addition to the radical scavenging, amifostine could also enhance DNA repair [104] and induce hypoxia [105] . Despite its approval and radioprotective effects (which are short term), amifostine is limited in use due its cumulative toxicity that is expressed as transient hypotension, nausea, vomit and allergic reactions.…”
Section: Ra Its Categoris and Mechanisms Of Functionmentioning
confidence: 99%
“…It was concluded that the radioprotective action of aminothiols may be mediated through a recombination-like mechanism, for which the diploid state and HR proficiency are required. A more recent study (42) demonstrated that the RecN gene product is required for amifostine-mediated DNA protection in E. coli cells. RecN protein is involved in homologous recombination, DSB repair (43), and structural maintenance of E. coli chromosome (44).…”
Section: Discussionmentioning
confidence: 99%